Analysis of Ni25at%Cr Debye-Waller Factor - Jahja, Aziz K.; Effendi, Nurdin (MESIN, 2007)
Analysis of Ni25at%Cr Debye-Waller Factor. Intensity analysis on X-ray diffractionexperiment was carriedout on Ni25at%Cr solid bulk sample to study the effect ofheat treatment on thephysical properties. Rietveld analysis (RIETAN) on both the untreated and heat-treated samplesincorporates both structural parameters such as Debye-Waller temperature factor and non-structuralparameters such as peak-position, peak-width, and peak broadening. Changes in these parameters havebeen observed in these samples, normally associated with changes in the materials properties after heattreatment,although previous residts show that the samplesmicrostructure and crystal group symmetryhave not been altered. Careful analysis revealed that on the atomic scale, the materials physicalcharacteristics such as Debye temperature, molar heat capacity, and homogenous and inhomogeneousstrain, thermal coefficient expansion have experienced some changes. Therefore this finding should havephysical impact onthe materials, such as convection-heat rate and thermal conductivity.